DETERMINATION OF THE EFFECT OF LEMON ADDITION UPON ELEMENT CONCENTRATIONS IN TEA - Ozdemir, Ozgul Dere; Kipcak, Azmi Seyhun; Derun, Emek Moroydor; Piskin, Sabriye (TAYLOR & FRANCIS INC, 2014)
Consumption of tea is a popular tradition in Turkey. In this article, non essential and toxic element concentrations were determined in infusions and lemon added infusions in widely consumed Turkish teas (black, earl grey, and green tea). Element concentrations were found to be in the order of aluminum>nickel>barium in black and earl grey teas. In green tea, the order was changed to aluminum>nickel>lead>barium. The concentrations of arsenic and antimony were below the detection limit of the inductively coupled plasma optical emission spectrometry method employed. The addition of lemon increased aluminum, cadmium, and lead concentrations in all teas whereas nickel concentration increased in black and green tea but decreased in earl grey. The barium concentration was same at all tea samples. In comparison with the recommended daily allowance ratios, the amount of aluminum consumed is between 13.167-24.396% in males and 17.556-32.528% in females for people who consume 200mL of teas daily. Other elements (cadmium, lead, nickel, barium) which are a concern for tea consumption were determined and the hazard index of daily tea drinking was found to be in the safe range except for green tea with lemon addition.
Keywords: hazard index; lemon; non essential; tea; toxic; GREEN TEA; INFUSIONS; LEAD; ALUMINUM; PRODUCTS; CADMIUM; LEAVES; Chemistry; Instruments & Instrumentation